Evaluation of Lactococcus lactis Isolates from Nondairy Sources with Potential Dairy Applications Reveals Extensive Phenotype-Genotype Disparity and Implications for a Revised Species - Cavanagh, Daniel (Appl Environ Microbiol, 2015)
Lactococcus lactis is predominantly associated with dairy fermentations, but evidence suggests that the domesticated organism originated from a plant niche. L. lactis possesses an unusual taxonomic structure whereby strain phenotypes and genotypes often do not correlate, which in turn has led to confusion in L. lactis classification. A bank of L. lactis strains was isolated from various nondairy niches (grass, vegetables, and bovine rumen) and was further characterized on the basis of key technological traits, including growth in milk and key enzyme activities. Phenotypic analysis revealed all strains from nondairy sources to possess an L. lactis subsp. lactis phenotype (lactis phenotype); however, seven of these strains possessed an L. lactis subsp. cremoris genotype (cremoris genotype), determined by two separate PCR assays. Multilocus sequence typing (MLST) showed that strains with lactis and cremoris genotypes clustered together regardless of habitat, but it highlighted the increased diversity that exists among “wild” strains. Calculation of average nucleotide identity (ANI) and tetranucleotide frequency correlation coefficients (TETRA), using the JSpecies software tool, revealed that L. lactis subsp. cremoris and L. lactis subsp. lactis differ in ANI values by ∼14%, below the threshold set for species circumscription. Further analysis of strain TIFN3 and strains from nonindustrial backgrounds revealed TETRA values of <0.99 in addition to ANI values of <95%, implicating that these two groups are separate species. These findings suggest the requirement for a revision of L. lactis taxonomy.